On Trajectories and Destinations of International Criminal Law Scholarship. (27th August 2015) - VASILIEV, SERGEY
Abstract : Taking up the torch from my fellow co-editors who have addressed substantive and methodological issues of international criminal law (ICL) in their contributions, I propose to turn to the current state and prospects of its scholarship. The moment is opportune for such a reflection. The questions raised by the production and dissemination of international legal scholarship were the leitmotif of past editorials and its (changing) role was chosen as the theme of the latest LJIL symposium. The professional functions of international legal scholars have been the subject of renewed interest and debate. To give an impulse to a similar debate in ICL, I will try to capture the zeitgeist of its academia and offer some observations on the positioning of scholarship vis-à-vis practice in ICL. Perspectives from this specialized field may enrich the existing conceptualizations of international legal scholarship and provide a new angle on its place within the profession.